Origin and ontogeny of the extrafloral nectaries associated to the inflorescences of Vigna Candida and Vigna Caracalla (Leguminosae, Phaseoleae) - Ojeda, Fabiana Soledad (2015)
Fil: Ojeda, Fabiana Soledad. Proplame-Prhideb (Conicet); Departamento de Biodiversidad y Biología Experimental, Facultad de Ciencia Exactas y Naturales, Universidad de Buenos Aires Intendente Güiraldes CABA, Argentina.